Exploring the global trade networks of the tungsten supply chain: Insights into the physical and monetary mismatch among countries. (1st January 2023) - Tang, Linbin; Wang, Peng; Ma, Zijie; Pauliuk, Stefan; Chen, Wei‐Qiang; Dai, Tao; Lin, Zipeng
Abstract: International trade is essential to bridge the imbalance between supply and demand of materials along with different nations effectively, especially for critical raw materials such as tungsten that are highly geographically unequally distributed. However, the international trade flows and their complex networks that link those participating nations have remained largely unexplored, which leads to inexplicable concerns for materials' criticality and their supply risks. By integrating the material flow analysis and the complex network analysis, this study traces the global trade flows of tungsten in various forms ranging from primary products to scrap among 223 countries and regions annually from 2000 to 2018 and explores the evolution of participating countries' role involved in international trade networks from both physical and monetary perspectives. We found that (1) there are ∼2673 thousand metric tons of tungsten feeding into supply chains globally during the 19 years, and about 96% of tungsten resources are re‐allocated from Asia to the high‐income regions; (2) the high‐income countries gain the potential benefits from both the resources and economic perspectives and they import 72% of tungsten resources in the form of primary and semi‐products from developing countries, meanwhile earning 87% of global tungsten trade value by exporting tungsten metal products with high value‐added back to those tungsten resources suppliers. Under the growing national interconnections of global tungsten trade networks, this study urges more cooperative actions and targeted supply chain management among the participating countries to secure the tungsten supply and sustainability of the global tungsten cycle.